Determination of the radiation background and the degree of radioactive pollution of different objects - Tymchuk, Alla; Slobodyan, Olga (My University, 2018)
The radiation background and the degree of radioactive contamination of various objects were determined in the work. Background radiation comes from both natural and man-made sources. For a year, 80% of which comes from nature. The remaining 20% is the result of exposure to man-made radiation sources, primarily medical images.
Keywords: radiation background; nuclear pollution; cosmic radiation; radon; кафедра технології молока і молочних продуктів; кафедра біотехнології і мікробіології